ENGINEERED NANO-MATERIALS FOR ENERGY AND THEIR POTENTIAL IMPACT ON ACTUAL ENVIRONMENTAL ISSUES - Popa-Simil, Liviu (International Journal of Research -GRANTHAALAYAH, 2021)
It is known for more than 2000 years that Damascus swords’ performances were not possible without the existence and usage of the “Damascus steel”, the first man made nano-hetero structural material that generalized is clearly showing that materials determine ultimate properties of the objects that made of. The actual world energy is manly based carbon emission materials, as coal, heavy oil, methane gas, with negative environment impact. Solar, wind and geothermal energy have also a negative impact on environment and have to be smartly used to minimize it. Nuclear energy, has lower CO2 emission, but because it is in its infancy it is complex, expensive and raises security and proliferation issues, has the potential for large scale accidents, and generates difficulties in dealing with waste fuel dispositioning. The novel developed families of engineered nano-materials, eliminate all the drawbacks of the actual nuclear power, rendering it among the most efficient and environmental friendly energy source. We learned from the global warming that the amount of energy man can produce on Earth is limited at 0.1% of sun delivered on Earth energy of 170 PW, which is of 200 TW, about 100 times more than today if it is chemical pollution free. Thermal pollution remains in place, therefore the upper clean power limit acceptable for the planet is at about 100 TW. The novel nuclear materials were developed in 6 families, each of them bringing in harmony a nuclear agent active inside that material as: - Micro-hetero structures, generally called “cer-Liq-Mesh”, that self-separates the fission products from the nuclear fuel and minimizes their fuel damage, allowing breed&burn to near perfect burning; - Nano-hetero structures generically called “CIci”, that form a super-capacitor, charged by nuclear energy and directly discharged as electricity; - Nano-clustered structure that enhances self-separation of transmutation products; - Fractal immiscible materials with radiation damage self-repairing capabilities eliminating the need for re-cladding in near perfect burning structures - Nano-structures with active NEMS used as fast control of nuclear reactivity by guiding neutrons in desired directions or ultralight shielding for mobile reactors. - Nano-structures that create active-quantum-nuclear-environment for long range nuclear reactions control by using quantum states entanglement and collective quantum states control. The use of these advanced materials in future nuclear energy related application will render a high efficiency, minimal nuclear waste, and optimal nuclear fuel cycle, delivering the needed planetary clean energy at will for the next 10,000 years.